Application of Kano Model in Priority Handling Aspects of the Tourism Offer in Sidomulyo Village, Batu City - Suharta, Amelia; Wijayanti, Wawargita Permata; Zakiah, Dwi Maulidatuz; Arifin, Muhammad Asfihan Nur; Barrett, Janine Lea; Simamba, Habeenzu (Perencanaan Wilayah dan Kota FT UB, 2023)
Sidomulyo Village is a tourist village with potential in Batu City, East Java. Even though Sidomulyo Village has natural charm and various attractions, its existence has yet to reach the attention of tourists widely. This is proven by a 32% decrease in tourists from 2018 to 2021. Apart from that, the duration of tourist visits to Sidomulyo Village is relatively short. This research aims to analyze priorities for handling tourism offer aspects using Kano model analysis. By filling in the gaps in research assessing the development stages and suitability of demand and supply in Sidomulyo Village, this research is expected to provide a contribution and understanding of handling priorities. It is hoped that the results of this research can improve aspects of the offerings in Sidomulyo Village, as well as provide a basis for further research in developing tourist villages. The research results show that 10 of the 27 research attributes have become a priority for the Sidomulyo Village management to improve aspects of the offer in the tourist village. The optimization of the priority, the number of tourist visits to Sidomulyo Village will increase, and it can become a superior flower tourism village in Batu City.